SOCIAL FORESTRY BUSINESS GROUP (KUPS) MARGO RUKUN BESTARI: THE TRANSFORMATION FROM POACHER TO CONSERVATIONIST - Suranto, Hadi; Gustriandha, Ryan Dwi; Pudja, Dadang Rachmat; Luthfan, Rezal; Nazah, Nurul Hidayatun; Rokmawati, Tuti (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to explain the impact of the Corporate Social Responsibility (CSR) program initiated by PT Pertamina Geothermal Energi Tbk (PGE) Ulubelu Area through a social forestry approach on the Margo Rukun Bestari Social Forestry Business Group (KUPS) in Ulubelu District, Tanggamus Regency, Lampung Province. This research uses a quantitative description method. This program prioritizes a circular interaction approach that includes profit and non-profit activities. The results showed that communities once involved in forest destruction activities are now transforming into proactive environmental conservationists. KUPS members, who are mostly former forest hunters, have succeeded in educating and inviting the surrounding community to be more aware of the importance of sustainable forest product management. The program has increased coffee farming productivity, improved degraded land, and increased community income. This initiative is a relevant model to be adapted in other regions with similar conditions.